Diseño de un sistema de cableado estructurado, con cable tipo ftp cat_6a (blindado) 4 pares para el nuevo hospital docente calderón de la ciudad de quito del Ministerio de salud pública (MSP) - Tutillo Cholango, Nelson René (2014)
This project aims to design a structured cabling system with CAT_6A FTP (Shielded cable) for different applications to be transmitted on the network in the new Calderon Teaching Hospital in the city of Quito. With this structured cabling system, the hospital can connect seamlessly with the various offices and hospitals of the Ministry of Public Health. If the implementation of a telephone system in VoIP (Voice over IP) calls should be done at zero cost with the other sites, because the voice would go through data links with zero cost for the use of this service (VoIP Phones). The first chapter covers the theoretical basis to understand the different concepts, standards and considerations to keep in mind in order to successfully carry out a design of a structured cabling system and its implementation….